Implementation and Analysis of Replicated Agent Based Load Balancing In Cloud Computing - Kaur, Parneet; Majithia, Sachin (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is growing as a new paradigm of large-scale distributed computing. It is an agenda for permitting appropriate, on-demand network access to a shared pool of computing resources. Load balancing is the foremost challenges in cloud computing which is vital to distribute the dynamic amount of workload through multiple nodes to confirm that no single node is overwhelmed. Cloud computing is an innovative technology which practices virtual machine instead of physical machine to manage, store and network the different mechanisms. In different virtual machines load balancers are used for assigning load in such a way that none of the nodes gets loaded heavily or lightly. The research area in load balancing is becoming more interested in the cloud computing. And through better load balancing in cloud, the performance is increased and user gets improved services. Here in this paper we have discussed different load balancing techniques along with the proposed technique used to solve the issue of data migration and data security using P-AES.